Recommendations for the Development of Sweet Corn Varieties (Zea mays saccharata, Sturt) for Several Planting area in Pekanbaru - Surtinah Surtinah; Niken Nurwati (Jurnal Pertanian Tropik, 2018)
Sweet corn is one commodity in great demand to day. Its production is very dependent on the variety in the plants and the location of planting. The aim of the study was to obtain varieties of sweet corn with high production, at suitable locations in Pekanbaru, which would be recommended for cultivation. The research method used is the experimental method with treatment design, namely the first factor is Variety which consists of 3 varieties of sweet corn, namely Sweet boy, Sweet Lady, and Bonanza, and the second factor is the location of planting, namely Rumbai Subdistrict, Bukit Raya District, and Marpoyan District peacefully. using factorial complete randomized design, with six replications. Observation parameters are weighted ear cob (g), ear length without weights (cm), the weight of cob without weighting (g), and sugar content of seeds (%). The data obtained were analyzed using Sidik Ragam and DMRT multiple distance test at the level of 5%. The recommendations givenfor planting in Rumbai Subdistrict are Sweet Lady varieties, for Bukit Raya District are Sweet Lady and Bonanza, and in Marpoyan Damai District are Sweet Boy varieties. The location that provides the highest sweet corn production is Bukit Raya, and the variety that provides the best production is Bonanza. Leaves of plants play a role in sweet corn production.